A NEW SPECIES OF GENTIANA (GENTIANACEAE) FROM THE SIKKIM HIMALAYA - Maity, D. (Edinburgh Journal of Botany, 2014)
Gentiana springateana D.Maity sp. nov. (Gentianaceae) is described from the Sikkim Himalaya and placed in G. section Phyllocalyx (Kusn.) T.N.Ho. This new taxon is described and illustrated, and compared morphologically with two related taxa, Gentiana phyllocalyx C.B.Clarke and G. urnula Harry Sm.
Keywords: Gentiana springateana D.Maity sp. nov.; Gentianaceae; Sikkim Himalaya